Development and Validation of a New Scale to Assess Attitudes and Perspectives Toward Persons With Disabilities - Youho Myong; Hyung-Ik Shin; Jeong-Eun Lee; Woosup Cho; You Gyoung Yi (Annals of Rehabilitation Medicine, 2021)
Objective To develop and validate a scale to assess people’s attitudes and perspectives toward persons with disabilities. Methods The three-stage development of the scale included a preliminary version drafted from the literature review and a nominal group process. Thereafter, the draft was examined further and revised through two rounds of Delphi survey by 16 disability experts. Lastly, the psychometric properties of the scale were assessed through an online survey of 1,359 employees at three university hospitals. Results A 32-item scale, defined after two Delphi surveys, was refined into 14 items with four subcategories: community integration, discomfort, charitability, and sense of burdening. The Cronbach’s alpha coefficient was 0.839 and domain reliability from 0.638 to 0.845. Recent education on disabilities yielded more positive attitudes toward persons with disabilities. Meaningful acquaintances with disabilities yielded more positive attitudes toward persons with disabilities. Conclusion This newly developed scale that measures attitudes toward persons with disability is reliable and valid. A future use of the scale could be to measure attitudinal improvements toward persons with disabilities after awareness education.